2022
DOI: 10.2169/internalmedicine.8385-21
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis Associated with Infective Endocarditis Showing Serological Positivity for PR3-anti-neutrophil Cytoplasmic Antibody and Anti-glomerular Basement Membrane Antibody

Abstract: We herein report a case of crescentic glomerulonephritis associated with infective endocarditis (IE). A 61year-old-woman presented with a fever and renal dysfunction and was diagnosed with IE. The patient was positive for PR3-ANCA and anti-GBM antibodies. Renal biopsy findings showed crescentic glomerulonephritis with isolated deposition of C3c, a serum conversion product of complement C3. Given these clinical findings, the patient was diagnosed with IE-associated glomerulonephritis. Antibiotic therapy was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Glomerulonephritis associated with IE is mainly due to vasculitis and less often to immune complex ( 8 ). Chiba et al reported a case of crescentic GN associated with IE; that case was positive for PR3-ANCA and anti-GBM antibodies ( 10 ). However, in the present case, MPO-ANCA and PR3-ANCA were both negative, and only GBM antibodies were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerulonephritis associated with IE is mainly due to vasculitis and less often to immune complex ( 8 ). Chiba et al reported a case of crescentic GN associated with IE; that case was positive for PR3-ANCA and anti-GBM antibodies ( 10 ). However, in the present case, MPO-ANCA and PR3-ANCA were both negative, and only GBM antibodies were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic findings in this study showed a decrease in complement activity in 56%, with reduced C3 only, reduced C4 only, or both in 37%, 3%, and 16%, respectively. Some patients also were reported with positive autoimmune serologies, mainly ANCA (28%) [18], and there is a report of positivity for PR3-ANCA and anti-GBM [19]. The primary pathology findings in endocarditis associated GN are focal crescents and necrotizing lesions.…”
Section: Diagnosis and Laboratory Evaluationmentioning
confidence: 99%
“…Early initiation of pathogen-directed antibiotic therapy is essential in managing glomerulonephritis secondary to acute endocarditis, aiming to curtail bacteremia and the associated immune response contributing to nephritogenic formation [19]. The use of combination antibiotic regimens with bactericidal synergism is advocated to sterilize bloodstream infections rapidly.…”
Section: Prevention and Treatment Strategiesmentioning
confidence: 99%